Is it possible predicting preeclampsia? - Gonzales Medina, Carlos Alejandro (2015)
Preeclampsia is a disease that appears only during human pregnancy and is associated toimportant maternal and perinatal morbidity and mortality. There is no integral model to predictpreeclampsia. A review on preeclampsia most predictive markers is performed includingDoppler velocimetry of the uterine arteries, biochemical markers and some associated clinicalfactors. A new preeclampsia prediction index proposal is reviewed.Keywords: Preeclampsia, pregnancy, prediction.